Sea Country Issue 1 1995 - (:unkn) unknown (Great Barrier Reef Marine Park Authority, 1995)
Sea Country, our new newsletter, will keep you up to date with sea country matters that are important to people on Cape York. Sea Country is written by staff from the Great Barrier Reef Marine Park Authority (GBRMPA) and the Queensland Department of Environment and Heritage (QDEH). Community Rangers (and your Councils) will pass them around, every month or two.
Keywords: Planning; Aboriginal communities; People and the Reef; Traditional owners